FACTORS INFLUENCING WILLINGNESS TO CONSUME GMF IN CHINESE POPULATION: THE MODERATING ROLE OF INFORMATION LITERACY - M. A. Nawaz; M. A. Anwar; R. Zhou; A. Nawaz; W. Dong; F. Asmi (Journal of Animal and Plant Sciences, 2019)
The study emphasized the factors affecting consumer perception regarding social valence view and consumer willingness to consume ‘Genetically Modified Food’ (GMF) in a Chinese population. The research highlighted the critical dominating role of ‘Health Concerns’ (toxins and genetic hazards) in consumer willingness of GMF consumption. Moreover, the GMF Labeling strongly influenced ‘Benefits Perceived’ (trust) in society towards GMF. The current study concludes the exciting moderating role of ‘Information Literacy’ as it can potentially enhance the consumers’ Willingness to Consume by decreasing their ‘Health Concerns’ and by increasing the ‘Benefits Perceived’. Further, it highlights the importance of effective communication strategy to convey the actual value of GMF to the society and stakeholders in the shortest possible time.
Keywords: Willingness to Consume; Health Concerns; Food Neophilia; Information Literacy; GM Labeling